The Role of Digital Literacy and Indonesian Language Proficiency Among University Students in Using Social Media - Dinihari, Yulian; Musringudin, Musringudin (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study examines how digital literacy and Indonesian language proficiency shape university students’ patterns of social media use. Digital literacy is conceptualized not merely as technical ability, but as a reflective and ethical capacity to access, evaluate, and produce information responsibly. Indonesian language proficiency is similarly positioned as a key indicator of students’ logical reasoning, clarity of expression, and politeness in digital communication. Using a mixed-methods approach with 75 Communication Science students, this study collected quantitative data through Likert-scale questionnaires measuring digital literacy, language proficiency, and ethical awareness, while qualitative insights were obtained from open-ended responses describing students’ verification practices, communicative strategies, and perceptions of responsible online behavior. The results show that 84% of students routinely verify information sources before sharing, 78% maintain polite and audience-appropriate language when interacting online, and 92% express pride in using proper Indonesian in digital spaces. These findings indicate that higher digital literacy is associated with stronger discernment, self-regulation, and ethical awareness in social media use, while greater Indonesian language proficiency supports clarity, civility, and context-sensitive communication. The integration of these competencies fosters responsible and reflective participation in online environments. The novelty of this study lies in demonstrating how language proficiency complements digital literacy in fostering responsible digital behavior and strengthening students' communicative ethics. Importantly, these insights have practical implications for curriculum development and character education in higher education, by promoting an integrated approach that combines digital literacy and language ethics to prepare students for responsible digital citizenship.